Positive control of cell division: FtsZ is recruited by SsgB during sporulation of Streptomyces - Willemse, Joost (Cold Spring Harbor Laboratory Press, 2011)
In bacteria that divide by binary fission, cell division starts with the polymerization of the tubulin homolog FtsZ at mid-cell to form a cell division scaffold (the Z ring), followed by recruitment of the other divisome components. The current view of bacterial cell division control starts from the principle of negative checkpoints that prevent incorrect Z-ring positioning. Here we provide evidence of positive control of cell division during sporulation of Streptomyces, via the direct recruitment of FtsZ by the membrane-associated divisome component SsgB. In vitro studies demonstrated that SsgB promotes the polymerization of FtsZ. The interactions are shown in vivo by time-lapse imaging and Förster resonance energy transfer and fluorescence lifetime imaging microscopy (FRET-FLIM), and are corroborated independently via two-hybrid studies. As determined by fluorescence recovery after photobleaching (FRAP), the turnover of FtsZ protofilaments increased strongly at the time of Z-ring formation. The surprising positive control of Z-ring formation by SsgB implies the evolution of an entirely new way of Z-ring control, which may be explained by the absence of a mid-cell reference point in the long multinucleoid hyphae. In turn, the localization of SsgB is mediated through the orthologous SsgA, and premature expression of the latter is sufficient to directly activate multiple Z-ring formation and hyperdivision at early stages of the Streptomyces cell cycle.